CONTENT OF PREPARATION OF MASTERS OF SOCIAL WORK FOR ORGANIZATIONAL-MANAGEMENT ACTIVITY - Ekaterina Yurievna Litvinova; Margarita Nikolaevna Konygina (Вестник Северо-Кавказского федерального университета)
The article actualizes the problem of organizing and managing social work as the most important direction in the formation of a modern system of social protection of the population and the practice of supporting and protecting those in need of social assistance. The basics of management and social organization are disclosed,and the features of the organizational and managerial activity of masters of social work are examined. The analysis of the empirical research (expert survey) of the specifics of the activity of the heads of the institutions of the social protection system of the population of the Stavropol Territory, as well as their educational needs in the field of organizational and managerial activity, is reflected. The author's position on the content of training masters of social work for organizational and managerial activity is presented.